2015
DOI: 10.1089/cyber.2014.0469
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Networking Sites for Relationship Maintenance in Long-Distance and Geographically Close Romantic Relationships

Abstract: Social networking sites (SNS) play an increasingly important role in maintaining geographically close romantic relationships (GCRR). However, knowledge about SNS use in long-distance romantic relationships (LDRR) is still lacking. The present study examined the relative importance of SNS in maintaining LDRR compared to GCRR, particularly with regard to the use of SNS to express involvement (via relational maintenance behaviors) and to gauge a partner's involvement (via partner surveillance and jealousy) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 33 publications
3
59
1
4
Order By: Relevance
“…Technology mediated communication (e.g., email, social networking sites) is also integral to maintenance and largely consists of self-disclosure, positivity, assurances, and social network discussions between partners (Dainton & Aylor, 2002;Johnson, Haigh, Becker, Craig & Wigley, 2008). Long-distance couples, for example, may use text messaging, Skype, or social networking sites to communicate more frequently and maintain relationships (e.g., Billedo, Kerkhof, & Finkenauer, 2015; see also Dargie, Blair, Goldfinger, & Pukall, 2015;Jiang & Hancock, 2013), whereas the lack of geographic proximity would have limited them in the past. Moreover, individual characteristics like humility are associated with some relationship maintenance processes (e.g., forgiveness) between long-distance partners, which suggests that partners' individual characteristics contribute to maintenance (Van Tongeren, Davis, & Hook, 2014).…”
Section: Maintenance In Long-distance Relationshipsmentioning
confidence: 99%
“…Technology mediated communication (e.g., email, social networking sites) is also integral to maintenance and largely consists of self-disclosure, positivity, assurances, and social network discussions between partners (Dainton & Aylor, 2002;Johnson, Haigh, Becker, Craig & Wigley, 2008). Long-distance couples, for example, may use text messaging, Skype, or social networking sites to communicate more frequently and maintain relationships (e.g., Billedo, Kerkhof, & Finkenauer, 2015; see also Dargie, Blair, Goldfinger, & Pukall, 2015;Jiang & Hancock, 2013), whereas the lack of geographic proximity would have limited them in the past. Moreover, individual characteristics like humility are associated with some relationship maintenance processes (e.g., forgiveness) between long-distance partners, which suggests that partners' individual characteristics contribute to maintenance (Van Tongeren, Davis, & Hook, 2014).…”
Section: Maintenance In Long-distance Relationshipsmentioning
confidence: 99%
“…Importancia que se acrecienta en las relaciones a más distancia, tal y como se reporta en un estudio comparativo entre parejas cercanas y lejanas, en términos geográficos. Las conclusiones reportan que para quienes vivían a corta distancia, la comunicación mediada a través de internet complementaba a la presencial; mientras quienes estaban más distantes tenían que esforzarse en sacar el máximo partido posible a la comunicación on line, por ser el único medio disponible para comunicarse y sostener la relación (Billedo, Kerkhof y Finkenauer, 2015). Quizás por ello, y tal y como indican estos autores, los internautas con relaciones de pareja a larga distancia, reportaban mayores niveles de compromiso en el mantenimiento de su relación a través de las redes sociales, que aquellos con relaciones cercanas geográficamente.…”
Section: Antecedentesunclassified
“…Al respecto, los usuarios que declaraban utilizar las redes sociales en sus relaciones a distancia, afirmaban que su propósito era fundamentalmente la vigilancia de la pareja y que experimentaban mayores niveles de celos en la red (Billedo et al, 2015). En otros estudios, incluso se relacionan las dinámicas de vigilancia y control a la pareja, con las violencias de género ejercidas a través de las tecnologías comunicativas (Gómez y Hueros, 2010;Muñiz-Rivas y Cuesta-Roldan, 2015).…”
Section: Antecedentesunclassified
“…On the other hand, Snapchat elicits higher levels of jealousy as compared to Facebook (Utz, Muscanell & Khalid, 2015). It has been found that SNS users involved in a romantic relationship and are geographically distant from each other experience more SNS jealousy and partner surveillance as compared to SNS users who are geographically close (Billedo, Kerkhof & Finkenauer, 2015).…”
Section: Facebook Usage and Facebook Jealousymentioning
confidence: 99%